Autointoxication and historical precursors of the microbiome–gut–brain axis. Issue 2 (23rd November 2018) - Mathias, Manon
ABSTRACT: This article focuses on autointoxication, a discredited medical theory from the late nineteenth century that provides important points of reflection for today's research on the role of microbes in the human gut for mental health. It considers how the theory of autointoxication, which came into great prominence amongst physicians and the general public worldwide, fell from grace by the middle of the twentieth century, and briefly asks why studies of the human microbiome are now back in vogue. It departs from earlier articles on the topic firstly by arguing that autointoxication theory was especially prevalent in France, and secondly by focusing on the application of this theory to mental health. Bringing to light medical treatises and theses from this period which have so far remained unexamined, it shows that examining the development and reception of medical theories form the past can help us today in understanding both the pitfalls and promise of research in this area.